The Meaning of Phoenician ḥsp in the Aḥirom Inscription - Watson, Wilfred G.E. (Folia Orientalia, 2026)
There is no agreement on the etymology and meaning of Phoen. ḥsp in the Aḥirom sarcophagus inscription, but the corresponding Egyptian verb ḥsb, “to break”, may help to resolve both issues. In support, several other words where Eg. /b/ corresponds to Semitic /p/ are discussed.